Innovative Artistic Strategies in Epistolary Fragments of Daniil Kharms (Linguistic Semiotic Aspect) - G. A. Krichevsky (Научный диалог)
The question of the evolution of epistolary prose is considered on the example of fragments of D.I. Kharms. Attention is paid to communication aspects using a linguo-semiotic approach. The results of the analysis of the epistolary passage of 1933 in comparison with other samples of imitative literary letters are presented. The question is raised about the similarity of the perception of the absurdity of D.I. Kharms and the absurdity in the Gogol tradition. The author, in particular, dwells on the theme of marriage and fairy tale elements in D.I. Kharms and N.V. Gogol. The emphasis is on the fact that D.I. Kharms demonstrated the failure of communication, including epistolary communication, while perceiving the surrounding world as absurd. To study an untitled epistolary fragment, among other things, a technique is used that fixes violations of the postulates of normal communication, which was proposed by O.G. Revzina and I. I. Revzin. As a result, it turns out that the artistic means of repetition used by D.I. Kharms violates both the postulate of the information content of normal communication and the postulate of the incompleteness of the description, which makes an effective epistolary dialogue impossible. The method of multiple repetition casts doubts on the effectiveness of the postulate of semantic coherence.